PENGEMBANGAN RENCANA KERJA PEMERINTAH DESA BERBASIS BUKTI MELALUI PELATIHAN METODE PRA DI WILAYAH BINAAN LEMBAGA JALIN NUSA: Promoting Evidence Based Village Government Action Plan through Training of PRA Method at Working Area of Jalin Nusa Institute - Kabul, Lalu Muh. (Yayasan Al-Amin Qalbu, 2024)
The aim of implementing services is to promote evidence based village government action plan through participatory rural appraisal (PRA) training at working area of Jalin Nusa Institute. The method used in implementing services consist of survey, promote training module, training implementation, monitoring and evaluation. The PRA training has been carried out for 3 days by using emancipatory adult education method and approach. According to the most of training participant (83.33 percent) training PRA has been well conducted. Before training, according to most of training participant (91.67 percent) that they have no knowledge and skill about PRA method. Meanwhile after training, according to most of training participant (93.33 percent) that they have gained a good knowledge and skill about PRA method